The Mediating Impact of Service Quality Towards Improving Sustainable Organizational Performance Private University in Indonesia - Ramaditya, Muhammad; Chandra, Galviano; Prasetyaningtyas, Sekar Wulan (Sekolah Tinggi Manajemen IPMI, 2024)
This study aims to determine the challenges of dynamics in the turmoil of sustainable transitions in the context of Organizational Performance at LLDIKTI 3 Jakarta Private University The independent variables used in this research are Organizational Change, Risk Management, Good University Governance, and ICT Competencies while the dependent variable used is Organizational Performance and also the mediating variable used is Service Quality. The methodology used in this study uses quantitative methods, implementation questionnaires via Google form, then the output data is collected for further protection. The population in this study is Private University with a total of 283 institutions, in the context of the University cluster there are 68 institutions. The sample in this study were 376 respondents. Instrument analysis applied to SmartPLS 3.0 with stratified random sampling method technique. .In order for higher education institutions to be managed effectively, openly, accountably, and able to implement their learning and research objectives, good university governance is very important. Here are some suggestions for effective Good University Governance such as continuous improvement is necessary for good governance, and this requires regular assessment of policies, practices, and procedures to ensure they remain relevant, efficient, and aligned with the agency's mission and goals.